PENGARUH METODE PEMBELAJARAN TPS TERHADAP KEMAMPUAN MENGANALISIS TUGAS MAHASISWA DISABILITAS NETRA DI PRODI PLB - Wijaya, Pipit Rika; Lailil Aflahkul Yaum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to explore in depth the influence of the Think-Pair-Share (TPS) learning method on the task analysis ability of visually impaired students in the Special Education (PLB) study program at Universitas PGRI Argopuro Jember (UNIPAR). This research employed a qualitative approach through a literature review, using scientific and relevant sources as the foundation for analysis. The results of this study reveal that the TPS method has a significant impact on visually impaired students in the classroom, particularly in enhancing their activeness, improving their understanding of the subject concepts, and developing their analytical thinking skills. The TPS learning method also fosters social interaction, which provides a safe space for visually impaired students to express and develop their opinions verbally and enables them to analyze learning content more deeply. The implications of this study emphasize to educators, especially in higher education, that cooperative and reflective approaches are essential components of inclusive learning activities. Therefore, cooperative and reflective approaches are highly recommended for implementation within the theme of inclusivity.